Evaluasi Kebijakan Pelaksanaan Pemberian Vaksinasi dalam Penanggulangan dan Pencegahan Penyebaran Covid-19 di Kota Bandung - Josep Dharmadi Buntoro; Wawan Kurniawan (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
The importance of the local government's role in overseeing the course of development and the economy in Indonesia is felt to be crucial, especially during the pandemic. The Government of Indonesia has declared COVID-19 a non-natural disaster in the form of a disease outbreak that must be mitigated to prevent an increase in cases. COVID-19 has an impact on almost all aspects of people's lives. The policy of the Government of Indonesia in handling and spreading COVID-19 is in the form of the Vaccine Procurement Program and the provision of COVID-19 Vaccinations as part of the Handling of COVID-19 and National Economic Recovery. The implementation of government programs cannot always run as expected. The policy in administering the COVID-19 vaccine can be interpreted as an effort by the local government to suppress and prevent COVID-19 so that it can be controlled. Implementation of the vaccination program if it is studied based on understanding Policy Implementation are actions taken either by individuals/officials or government or private groups directed at achieving the goals outlined in policy decisions.